Gender and Racial Differences: Development of Sixth Grade Students' Geometric Spatial Visualization within an Earth/Space Unit. (November 2015) - Jackson, Christa; Wilhelm, Jennifer Anne; Lamar, Mary; Cole, Merryn
<x xml:space="preserve">Abstract</x> This study investigated sixth‐grade middle‐level students' geometric spatial development by gender and race within and between control and experimental groups at two middle schools as they participated in an Earth/Space unit. The control group utilized a regular Earth/Space curriculum and the experimental group used a National Aeronautics and Space Administration‐based curriculum. The quantitative data sources included the Lunar Phases Concept Inventory, Geometric Spatial Assessment, and the Purdue Spatial Visualization–Rotation Test. The results indicated the experimental males and females, and the students of color and white students in the experimental group showed significant gains in their understanding of geometric spatial visualization from pre‐ to post‐implementation. However, for the control group, the significant gains were limited to the males and the white students. The findings reveal that support is needed for males, females, and all racial groups to have the opportunity to develop their spatial reasoning, which in turn, increases students' scientific understanding.